bahasa inggris bahasa inggris: bahasa inggris - Kiki Endah; Endah Vestikowati; Candra Firmanto; Wenny Dastina (Interdisciplinary International Journal of Conservation and Culture, 2025)
This study aims to develop an integrative model for smart rural tourism development by leveraging a community-based green economy and local wisdom in the Sukapulang Agrotourism Area, Sukasetia Village, Indonesia. Amidst accelerating digitalization, this research argues that socio-cultural foundations are key determinants for sustainable development. Using a qualitative case study design, data were gathered through in-depth interviews with ten key informants (village officials, Pokdarwis managers, and MSME actors), participant observation, and documentation. Data analysis was conducted through thematic coding, categorizing the dimensions of empowerment, green practices, and cultural values, and was validated through source triangulation. The findings indicate that smart tourism in Sukasetia is driven by the spirit of "Gotong Royong" (mutual cooperation) and an agrarian cultural heritage that serves as an ethical filter for green economy implementation. This study proposes an integrative model in which local wisdom serves as the foundation, community empowerment as the primary driver, and digitalisation as the accelerator. The novelty of this research lies in repositioning the "smart" paradigm from mere technological adoption to a governance approach grounded in cultural sovereignty.